2022
DOI: 10.1155/2022/5860671
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress-Related Four-Biomarker Risk Classifier for Survival Evaluation in Esophageal Cancer

Abstract: Purpose. Esophageal cancer (EC) is a lethal digestive tumor worldwide with a dismal clinical outcome. Endoplasmic reticulum (ER) stress poses essential implications for a variety of tumor malignant behaviors. Here, we set up an ER stress-based risk classifier for assessing patient outcome and exploiting robust targets for medical decision-making of EC cases. Methods. 340 EC cases with transcriptome and survival data from two independent public datasets (TCGA and GEO) were recruited for this project. Cox regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that BCAP29/31 is required for optimal targeting of MHC-I molecules to ER exit sites, as well as for proper traffic from ER to Golgi [6]. At the same time, BCAP29/31 exhibits carcinogenic effects in a variety of tumors, and this effect is mainly manifested by promoting the metastasis and proliferation of tumor cells [33]. However, the specific role and mechanism of BCAP29/31 in HNSC have not been clarified in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that BCAP29/31 is required for optimal targeting of MHC-I molecules to ER exit sites, as well as for proper traffic from ER to Golgi [6]. At the same time, BCAP29/31 exhibits carcinogenic effects in a variety of tumors, and this effect is mainly manifested by promoting the metastasis and proliferation of tumor cells [33]. However, the specific role and mechanism of BCAP29/31 in HNSC have not been clarified in detail.…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily localized in the mitochondria and contains three serine residues, which could be activated by four inhibitory PDHK1-4 and two reactivated phosphatases (PDP1-2). These PDP1-2 are reversibly phosphorylated and regulate glycolysis and TCA [19,20]. Spakova et al demonstrated that silencing HIF-1α/miR210 expression increases PDHA1 and decreases MITF-M expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ER processes were found to be highly associated with tumor progression [ 4 ]. The ER, which is the largest protein processing organelle in cells, can precisely regulate the whole process of protein synthesis and transportation [ 5 ]. ER function can be disrupted by numerous abnormal cellular states, which causes ER stress [ 6 ].…”
Section: Introductionmentioning
confidence: 99%